2021
DOI: 10.1093/genetics/iyab034
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian modeling of skewed X inactivation in genetically diverse mice identifies a novel Xce allele associated with copy number changes

Abstract: Female mammals are functional mosaics of their parental X-linked gene expression due to X chromosome inactivation (XCI). This process inactivates one copy of the X chromosome in each cell during embryogenesis and that state is maintained clonally through mitosis. In mice, the choice of which parental X chromosome remains active is determined by the X chromosome controlling element (Xce), which has been mapped to a 176 kb candidate interval. A series of functional Xce alleles has been characterized or inferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…Overall, six competing Xce alleles have been proposed, with the order of strength being a < f < e < b < c < d, where Xce a is the most likely to be inactivated and Xce d the least likely. A new study has identified an additional allele, reportedly the weakest in the Xce allelic series [145]. In Xce heterozygotes, the X chromosome carrying the weaker of the two alleles is more likely to be inactivated.…”
Section: Preferences In Choice: Random XCI Patterns Are Often Skewedmentioning
confidence: 99%
“…Overall, six competing Xce alleles have been proposed, with the order of strength being a < f < e < b < c < d, where Xce a is the most likely to be inactivated and Xce d the least likely. A new study has identified an additional allele, reportedly the weakest in the Xce allelic series [145]. In Xce heterozygotes, the X chromosome carrying the weaker of the two alleles is more likely to be inactivated.…”
Section: Preferences In Choice: Random XCI Patterns Are Often Skewedmentioning
confidence: 99%
“…Furthermore, the CC-RIX can be used to detect parent-of-origin effects using reciprocal F1 designs (Oreper et al . 2018; Sun et al . 2021), though we do not investigate these approaches here.…”
Section: Discussionmentioning
confidence: 99%
“…The complex population structure of the CC-RIX reduces mapping power, but does enable more accurate estimation of additive heritability. Furthermore, the CC-RIX can be used to detect parent-of-origin effects using reciprocal F1 designs (Oreper et al 2018; Sun et al 2021), though we do not investigate these approaches here. These key principles should also extend to MPPs (and more broadly any mapping population) of other organisms with similar experimental features ( e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, six competing Xce alleles have been proposed, with the order of strength being a<f<e<b<c<d, where Xce a is the most likely to be inactivated and Xce d the least likely. A new study has identified an additional allele, reportedly the weakest in the Xce allelic series (Sun et al, 2021). In Xce heterozygotes, the X chromosome carrying the weaker of the two alleles is more likely to be inactivated.…”
Section: Preferences In Choice: Random XCI Patterns Are Often Skewedmentioning
confidence: 99%